Right to private life under the scope of mass surveillance: differences in approaches to the implementation of the principle of proportionality in the jurisprudence of the CJEU and the ECtHR - Hartmane, Valērija Ruta (Riga Graduate School of Law, 2023)
Mass surveillance in a digital age prompts a new domain of challenge in the balancing act of the interest of national security and the right to privacy. The Thesis examines the clash between national security imperatives and the right to privacy by employing mainly a comparative approach. The author establishes the following research question: what are the approaches on implementing a principle of proportionality of the ECtHR in the case of Big Brother Watch and the CJEU in the case of Schrems I and Schrems II? The examination of landmark cases illuminates the need for safeguarding measures and a proactive approach to privacy protection. The main prerequisites for finding the balance between respective interests, inter alia, intervention with one’s privacy shall be strictly necessary and safeguarded on all levels by adequate mechanisms.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; European Court of Human Rights; Court of Justice of the European Union; mass surveillance; right to privacy